Early Efficacy Assessment of Arthroscopic Lower Trapezius Transfer With Tendon Autograft in the Management of Massive Irreparable Posterosuperior Rotator Cuff Tears - Ye, Lingchao; Han, Dawei; Zhang, Qingguo; Yang, Xiangdong; Tung, Tao-Hsin; Zhou, Xiaobo (Frontiers in Surgery, 2022)
Objectives: To explore the indications and surgical techniques for arthroscopic lower trapezius transfer (LTT) with tendon autograft in managing massive irreparable posterosuperior rotator cuff tears (PSRCTs); to compare the patients’ postoperative pain scale, range of motion, and functional scores with conventional repair procedures of massive rotator cuff tears (RCTs); and to validate the feasibility, safety, and efficacy of this technique. Methods: This study retrospectively enrolled 23 patients with massive irreparable PSRCTs, admitted to and followed up by the Taizhou Hospital of Zhejiang province between July 2020 and April 2021, and treated with ipsilateral LTT and ipsilateral hamstring tendon autograft. The control group consisted of 23 patients with massive RCTs receiving conventional repair procedures within the same frame. Follow-up data at the preoperative visit, postoperative day 1, and postoperative month 3 were collected to assess the range of motion in the shoulder and the post-operative MRI results, all of which could provide a comprehensive postoperative early efficacy assessment. Results: Follow-up visits were completed for all patients, revealing improvements in all aspects compared to the preoperative state, with no complications, such as postoperative infection of surgical sites and nerve injuries. Three months after operation, the distribution of shoulder range of motion of patients with two types of operation was as follow: angles of flexion and lifting (142.39°±27.67° vs. 132.39°±27.67°), abduction (142.17°±24.95° vs. 129.78°±31.21°), external rotation at side (71.74°±10.81° vs. 66.96°±10.84°), external rotation at 90° abduction (70.22°±14.49° vs. 66.09°±11.96°), visual analog scale (VAS) on the first day after surgery (0.83±0.57 vs. 2.04±0.76); VAS in March after surgery (0.57±0.728 vs. 1.61±1.03), Constant–Murley (57.04±14.32 vs. 56.22±13.86), UCLA shoulder score (25.00±3.60 vs. 20.96±5.33), Subjective Shoulder Value (SSV) (72.23±12.1 vs. 53.16±13.8). Significantly better improvements were found in the study group, including better range of motion and lower VAS on postoperative day 1 and month 3, Constant–Murley score, UCLA shoulder score, and SSV (P<0.0001). Conclusion: Compared to conventional repair procedures, in the early postoperative period, LTT with tendon autograft could achieve better pain relief, more rapid motor functional recovery, and higher functional scores for massive irreparable PSRCTs.